Alsangen 1940 - Nielsen, Puk Elmstrøm (Passage - Tidsskrift for litteratur og kritik, 2011)
Puk Elmstrøm Nielsen: “Community Singing” In 1940, during the first summer of the German occupation, Denmark experienced a surge of nationalism. This manifested itself in several well attended meetings, alsang, where the Danes expressed their national feelings through singing. This article analyses the songs and describes how alsang became a manifestation of the idea of a national community in which the people was not divided by social, cultural or economic interests. Furthermore it is discussed to what extent alsang was anti-German.